2021
DOI: 10.7324/japs.2021.110904
|View full text |Cite
|
Sign up to set email alerts
|

Direct Medical Cost of Treatment of uncomplicated malaria after the Adoption of artemisinin-Based Combination Therapy in Nigeria

Abstract: Globally, malaria continues to have clinical importance and economic impact. There is insufficient data on direct medical costs of malaria treatment at healthcare facilities since the adoption of artemisinin combination therapies (ACTs) in Nigeria. The study aimed to assess the direct medical cost incurred by patients with uncomplicated malaria disease after the adoption of ACTs. The study was retrospective. Data were collected from malaria patients' folders between January 2014 and June 2018 in two secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The median prices of surveyed products are higher than in earlier years and may potentially be linked to the end of the AMFm and PSCM projects, where quality-assured malaria medicines were subsidised (Ebere Emilia et al, 2021 ; Ezenduka et al, 2013 ; Ezenduka et al, 2014 ), or COVID-19 pandemic, which has been suggested to be responsible for more than a 50% rise in the price of essential medicines in Nigeria (Emmanuel Awucha et al, 2020 ). A study after the subsidy project suggests the continued impact of the project on prices of ACTs (Akulayi et al, 2017 ) thus COVID 19 pandemic may be a major contributing factor to the higher prices observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The median prices of surveyed products are higher than in earlier years and may potentially be linked to the end of the AMFm and PSCM projects, where quality-assured malaria medicines were subsidised (Ebere Emilia et al, 2021 ; Ezenduka et al, 2013 ; Ezenduka et al, 2014 ), or COVID-19 pandemic, which has been suggested to be responsible for more than a 50% rise in the price of essential medicines in Nigeria (Emmanuel Awucha et al, 2020 ). A study after the subsidy project suggests the continued impact of the project on prices of ACTs (Akulayi et al, 2017 ) thus COVID 19 pandemic may be a major contributing factor to the higher prices observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Huge out-of-pocket expenditures are made on health and education, as well as an array of other non-food items such as transport, fuel, electricity, household items, and clothing (The World Bank, 2022a, p. 11-14) The current World Health Organisation (WHO) national health account data on financing schemes as a percentage of current health expenditure (CHE) for the year 2020 estimates that in Nigeria, OOPS accounts for approximately 75%, while government schemes and compulsory contributory (social) health insurance schemes account for about 15% and 1%, respectively (WHO, 2023;The World Bank, 2023). This structure of healthcare financing which relies heavily on OOPS has not only proven to be unprogressive, and financially unprotective of the poor but also promotes inequality and catastrophic health spending, as well as impoverishment of the vulnerable group and the poor who live below US$2 a day (Adekunle, 2022; Ayogu et al, 2021;Olakunde, 2012;Oyibo, 2011). Fortunately, the recently signed National Health Insurance Authority Act (2022) gives a ray of hope to the poor and vulnerable.…”
Section: Health Funding System In Nigeriamentioning
confidence: 99%
“…It is responsible for catastrophic personal healthcare spending, and loss of income as a result of absence from work. A large portion of the OOPS segment of the total health expenditure of Nigeria is due to malaria (Ayogu et al, 2021). Thus, reducing the malaria epidemic in the country will contribute greatly to the principles of UHC and the attainment of the already outlined SDGs (Adelakun, 2022).…”
Section: Malaria Morbidity and Mortality As Major Health Outcomes Of ...mentioning
confidence: 99%
See 2 more Smart Citations